Calcimimetic use in US hemodialysis facilities in first 2 years after the launch of etelcalcetide: A descriptive analysis of real‐world clinical practice and outcomes. Issue 2 (20th December 2021) - Stephens, John Mark; Fox, Kathleen M.; Desai, Pooja; Cheng, Sunfa; Goodman, William G.; Kendrick, Jessica B.
Abstract: Introduction: This study described control of parathyroid hormone (PTH), phosphorus, and corrected calcium in adults initiating calcimimetics in small dialysis organizations after the introduction of etelcalcetide. Methods: This retrospective study using Visonex Clarity electronic health records between October 1, 2017, and December 31, 2019, identified adults ≥ 18 years of age receiving in‐center hemodialysis as either a cinacalcet or etelcalcetide initiator based on their first calcimimetic use in 2018 (index date) with no prior calcimimetic use in the 3 months preindex date. Patients were stratified by PTH at index date and were followed for 15 months. Subcohorts of patients who were persistent on a single calcimimetic for 15 months and of patients who had their calcimimetic changed from cinacalcet to etelcalcetide were also analyzed. Findings: A total of 677 patients initiated cinacalcet and 711 initiated etelcalcetide. Mean PTH (pg/ml), phosphorus, and corrected calcium (mg/dl) at baseline were 864, 5.9, and 9.3 for cinacalcet and 804, 5.9, and 9.4 for etelcalcetide, respectively. During follow‐up, the proportion of initiators considered in‐target (monthly average PTH < 600) increased from 48% to 62% with cinacalcet and from 56% to 86% with etelcalcetide in the baseline PTH 600 to < 800 subgroup; increased from 30% to 64% with cinacalcet and 31% to 59% with etelcalcetide among those with baseline PTH 800 to < 1000; and increased from 14% to 41% with cinacalcet and 12% to 58% with etelcalcetide among those with baseline PTH ≥1000. A similar pattern was observed for persistent users (n = 646). For patients changed from cinacalcet to etelcalcetide (n = 183), the proportion of patients considered in‐target increased from 22% in the month prior to the treatment change to 51% in Month 6 postchange. Discussion: Patients initiating calcimimetics at lower baseline PTH had better biochemical control than patients starting at higher PTH. Patients changed from cinacalcet to etelcalcetide had improvements in PTH control postchange.